Digital Marketing as a Strategy to Enhance Image and Patient Visits in Healthcare Facilities - Mujtahidah (Journal of Scientific Insights, 2025)
Digital marketing has emerged as a key strategy in the healthcare sector to reach communities, build institutional image, and increase patient visits. The shift in consumer behavior toward digital platforms has driven healthcare facilities to adopt technology-based marketing approaches. This study aims to review and analyze the role of digital marketing in enhancing the image of healthcare facilities and its impact on patient visits. This research is a narrative literature review analyzing ten scientific articles published between 2019 and 2024. Literature was collected from national and international databases using keywords related to digital marketing, institutional image, and patient visits in healthcare services. The review indicates that digital marketing strategies such as social media, educational content, search engine optimization (SEO), and online testimonials significantly contribute to enhancing institutional image and patients’ intention to visit. The institutional image built through digital media plays a crucial role in fostering trust, loyalty, and decision-making in utilizing healthcare services. Digital marketing holds great potential as a strategic instrument in healthcare facility promotion. A more systematic integration, along with the readiness of resources and supportive policies, is required to ensure the optimal and sustainable implementation of this strategy.